2014
DOI: 10.3382/japr.2013-00761
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different sources and levels of selenium on performance, meat quality, and tissue characteristics of broilers

Abstract: Background: Several studies indicated that dietary organic selenium (Se) usually absorbed better than an inorganic source, with high retention and bioavailability. Dietary Se as an antioxidant element affects the immune system and hematological status in animals. Therefore, the aim of this study was to evaluate the effect of dietary supplementation of bacterial selenium as an organic source on hematology, immunity response, selenium retention, and gut morphology in broiler chickens. Results: The present result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
50
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 19 publications
9
50
1
Order By: Relevance
“…Additionally, the results showed increasing Se concentrations in the liver, kidney, and breast muscle with increasing Se supplementation from HPSeKS (Table 5). Oliveira et al [6] also found the deposition of Se in liver and breast muscle of broilers that increased linearly (p<0.05) with increasing dietary levels of Se from Se-enriched yeast.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Additionally, the results showed increasing Se concentrations in the liver, kidney, and breast muscle with increasing Se supplementation from HPSeKS (Table 5). Oliveira et al [6] also found the deposition of Se in liver and breast muscle of broilers that increased linearly (p<0.05) with increasing dietary levels of Se from Se-enriched yeast.…”
Section: Discussionmentioning
confidence: 87%
“…The previous reports revealed that the supplements of inorganic Se from sodium selenite [25] and organic Se from Seenriched yeast [6,[26][27][28][29], selenomethionine [30], Se-enriched plants [10], and Se-enriched alga [8] did not change the productive performance of broilers. Similarly, productivity of broilers in this trial was not altered by Se supplementation, although the supplemental level of Se from HPSeKS was up to 2.0 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that increased body weight of commercial goose received organic selenium was observed (Lukaszewicz et al, 2013) and also in broilers (Kinal et al, 2012). Many researchers reported that the Se-yeast has more efficient influence in depositing selenium to the liver and breast muscle (Marcel et al, 2014;Oliveira et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Selenium (Se) is an essential trace mineral known to possess antioxidant and has a profound impact on several physiological functions and productivity. Selenium, as a part of an antioxidant enzyme (Upton et al, 2009;Surai and Fisinin, 2014), detoxifies oxygen radicals and peroxides (Oliveira et al, 2014), and can reduce heat stress caused by tropical environment climate (Ibrahim et al, 2011;Yuan et al, 2012). Organic Se commonly used in the diets of broiler chickens can be derived from yeast.…”
Section: Introductionmentioning
confidence: 99%